Improvement of Cotton Reception and Storage Technology - Salimov, O.; Salimov, A. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information on improving the technology of harvesting and storing cotton at cotton harvesting points. When storing raw cotton with moisture and weediness above the norm, lead to biological and mechanical destruction of fiber and seeds. In the process of self-heating, raw cotton loses its fiber yield due to the destruction of its bond with the seed, and the processing of such cotton increases the loss of free fibers to waste. Taking into account the research results, improve the technologies for processing raw cotton and the preparation and storage of products.